Cost of each Team GB Olympic medal revealed - Walker, T. (Sportsmanagement, 2016)
The average cost of a Team GB Olympic medal has been calculated at £4.29m (€4.75m, US$5.25m) - with gymnastics and shooting finishing as the most cost-effective Olympic sports and hockey and sailing the most expensive.